(untitled) (Research, Society and Development, 2024)
Hyperglycemia is a common occurrence in the hospital environment and is associated with negative outcomes. Diabetes Mellitus has a high prevalence among hospitalized patients, and the management of hyperglycemia in the hospital environment for these patients differs from outpatient management. The use of sliding scale as isolated therapy in patients with persistent hyperglycemia is contraindicated; however, many hospitals use this scheme due to its ease. The study aimed to describe and group the different insulin regimens used in the hospital by diabetic patients, profile these patients, identify episodes of hyperglycemia and hypoglycemia and quantitatively evaluate the presence of capillary blood glucose data in the electronic medical record. A retrospective observational research was carried out in a university hospital that collected data for four months and selected all diabetic patients admitted to the neurological, infectious, medical and long-stay clinics. Some of the results obtained showed that: the most prevalent comorbidity, in addition to diabetes, was high blood pressure; the most frequent reason for hospitalization was stroke; the main regimen initially prescribed for patients was the sliding scale; the occurrence of hypoglycemia was identified in 13 patients and the average number of tests performed and registered in the electronic system compared to the prescribed number of blood glucose tests was 84.4%. This study contributed to a better understanding of how insulin treatment is carried out for diabetic patients in the hospital.